Carpal Tunnel Syndrome Associated with Klippel-Trénaunay-Weber Syndrome: A Case Report. Issue 2 (April 2015) - Siegall, Evan; Ratner, Joshua
Abstract : Case: A fourteen-year old patient with Klippel-Trénaunay-Weber syndrome presented with an eleven-year history of pain and subjective weakness in the median nerve distribution of the hand. Electromyography studies demonstrated chronic denervation, and magnetic resonance imaging ruled out vascular malformations as a cause of extrinsic compression. Despite the chronic compression of the median nerve within the carpal tunnel and known complications associated with Klippel-Trénaunay-Weber syndrome, a surgical release was performed. Conclusion: Postoperatively, the patient noted immediate pain relief. At the time of the three-year follow-up, the subjective strength and function of the hand were greatly improved compared with the preoperative status. Even with symptoms suggesting decade-long compression, carpal tunnel release can be a safe and beneficial treatment for patients with Klippel-Trénaunay-Weber syndrome.